CARACTERÍSTICAS DA CONSTRUÇÃO SUSTENTÁVEL NO BRASIL: A PERSPECTIVA DOS INCORPORADORES - Abreu, Isabel Cristina Rosa (2012)
This dissertation covers research into the characteristics of sustainable construction in Brazil according to the perspective of property developers, because they are who retain the power of decision over whether to construct on a sustainable basis or not. The method of research is exploratory, bringing together the theoretical and empirical approaches. A sample comprising 10 Brazilian property development companies located in the cities of Rio de Janeiro and São Paulo was selected. This sample forms a significant proportion of the property development sector based on business done. The criteria for the definition of the sample met the requirements of convenience sampling. Theoretical references from several authors have shown that the concept of sustainable construction is growing strongly worldwide, and Brazil is accompanying the trend. During the analysis of the empirical approach to this study, which was carried out using a questionnaire and semi-structured interviews, it was concluded that, in the perspective of the property developers, the most important characteristic in sustainable construction in Brazil is the rational use of water. The demotivating and motivating factors of greatest relevance in the implantation of sustainable construction in Brazil are the costs of the work and the economic, social and environmental benefits respectively. These results are considered appropriate for the reality of Brazilian civil construction, as it is intended to clarify during the course of the work.